Living in a changing world: an integrated approach to documenting and understanding medium to long-term vegetation changes in three contrasting land use systems in a mesic savanna, Nothern Zululand, South Africa - Wigley, Benjamin J (Department of Biological Sciences, 2023)
There is an increasing amount of evidence suggesting that the balance between trees and grasses in savannas and grasslands has been disrupted in the recent past. Numerous studies from around the world have reported an increasing woody component at the expense of the grass layer. The causes most frequently cited for this shift are linked to changing land use practices. This study was therefore set up to investigate the effects of three contrasting land use systems on long-term vegetation dynamics in a mesic savanna. I aimed to determine if land m;e practices alone could account for the changes in vegetation cover evident at the study sites between 1937 and 2004. An alternative explanation for the changes could be linked to a global driver such as changing climate or increasing atmospheric CO2 concentrations. The rate and extent of vegetation changes were measured and recorded in areas that have remained under communal, commercial and conservation tenure for approximately the past century. Changes in vegetation were determined for a 25 km2 area in each area using repeat panchromatic aerial photography from 193 7, 1960 and 2004. Images were mosaicked and georeferenced then overlaid and manually classified. A comparison between manual classifications and machine-generated classifications using eCognition software was also undertaken. Past land use practices for the three study areas were reconstructed using a combination of archive materials and oral histories. The managers, land users or landowners from areas under communal, commercial and conservation tenure were extensively interviewed to determine their perceptions of the changes, consequences of the changes and reactions to the changes in vegetation. The results showed that significant increases in woody cover occurred during the 67-year period at all three sites. The communal study site showed the least increase in tree cover. However, the overall increase in tree cover at the communal site, from 6.2 to 25.7 % (fourfold increase), is still a highly significant change. The greatest increase in tree cover was evident at the commercial study site where tree cover increased seventeen fold. Total tree cover increased from 2.7 to 50.8 % during the 67-year period. The increase in tree cover at the conservation study site was also highly significant. Tree cover increased by ~360 %, from 14.7 % in 1937 to58.5 % in 2004. These vegetation changes correspond to major losses of grassy habitats in each area. The biodiversity losses associated with these changes are largely unknown but are likely to be substantial. Past land use practices and histories in each area were also shown to be significantly different with major differences in human densities, stocking rates, herbivore feeding types and burning practices. Long-term rainfall records did not show any significant changes in the quantity or seasonality of rainfall. The results suggest that past land use practices did have some impact on the type of and extent of bush encroachment. The study found that although the land users were aware of and concerned about the changes in woody cover in each area, they were not doing much to combat these changes. The perceived importance of the different causes of woody increase was also found to be substantially different amongst the different land users. The findings suggest that land use practices alone cannot explain the widespread occurrence of bush encroachment in the area. This could suggest that a global driver is contributing to the increasing tree component.